1996
DOI: 10.1161/01.cir.93.3.502
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ‘Incisional’ Reentrant Atrial Tachycardia Complicating Surgery for Congenital Heart Disease

Abstract: Successful ablation of intra-atrial reentrant tachycardia complicating surgery for congenital heart disease may be achieved by creation of an ablative lesion in a critical isthmus of conduction bounded by anatomic barriers. This isthmus may be identified by the presence of entrainment with concealed fusion and an analysis of the relationship between the postpacing interval and the tachycardia cycle length and between the activation time and the stimulus time. Because this isthmus is invariably confined on at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(209 citation statements)
references
References 25 publications
5
203
0
Order By: Relevance
“…Classically, PPI is expected to be the sum of the times required for the paced wave front to travel to and from the reentrant circuit plus the TCL. 6,8 However, if the pacing site is within or near a bystander reentrant loop that shares a common segment or isthmus with the true reentrant circuit, it is possible that the paced wave front takes different propagation pathways to and from the true reentrant circuit. Therefore, the return cycle at that site after the last paced beat of entrainment pacing may not include the entire TCL but instead represents the revolution time around the bystander reentrant loop itself.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, PPI is expected to be the sum of the times required for the paced wave front to travel to and from the reentrant circuit plus the TCL. 6,8 However, if the pacing site is within or near a bystander reentrant loop that shares a common segment or isthmus with the true reentrant circuit, it is possible that the paced wave front takes different propagation pathways to and from the true reentrant circuit. Therefore, the return cycle at that site after the last paced beat of entrainment pacing may not include the entire TCL but instead represents the revolution time around the bystander reentrant loop itself.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies in patients with AT after surgical repair are generally performed for stable AT, allowing easy identification of the reentrant circuit [1] [2]. In this patient, however, AT could not be induced despite any provocation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial tachycardia (AT) is observed occasionally in patients after atriotomy for surgical repair of heart disease [1] [2]. Sustained AT generally results from macroreentry around the atriotomy scar and cavotricuspid isthmus (CTI)-dependent atrial flutter (AFL).…”
Section: Introductionmentioning
confidence: 99%
“…Standard definitions were used to define successful tachycardia entrainment. 6,9,10 The PPI was measured from the last stimulus artifact to the beginning of the first rapid deflection of the RVA electrogram.…”
Section: Entrainment Pacing Protocolmentioning
confidence: 99%
“…9,10 We postulated ( Figure 1) that BBR-VT entrainment pacing from the right ventricular apex (RVA) should result in a PPI similar to the tachycardia CL (TCL) because the right bundle-branch distal insertion is in this anatomic area. This approach may differentiate BBR from other mechanisms of wide-QRS-complex tachycardia with AV dissociation, 3,11 such as ventricular myocardial reentry (MR) or AV nodal reentry (AVNR), where the circuit is usually away from the RVA.…”
mentioning
confidence: 99%